Modulation of the Renin-Angiotensin System: A Novel Exercise Analyzer Approach. - Mubeen Ahmed; Khan, Alamgir; Zafar Iqbal Butt; Bilal Rasool; Muhammad Saleem Akhtar; Muhammad Hamza; Shamshaid Ahmed; Mehmet Dalkılıç (International Journal of Endorsing Health Science Research, 2025)
Background: The Renin-Angiotensin System (RAS) is a vital regulatory system that maintains electrolyte balance and blood pressure, playing a potential role in physical activity regulation. This study investigates the effects of moderate-intensity exercise on plasma renin levels using a novel, self-made exercise analyzer. Methodology: An experimental research design was implemented. Healthy male students were randomly selected from the University of the Punjab (PU), Lahore, Pakistan. Participants were divided into two groups: the Control Group (CG) and the Experimental Group (EG), each consisting of five participants. Ethical approval was obtained from the University’s ethical review board. The EG underwent an eight-week moderate-intensity exercise intervention. Plasma renin levels were measured pre- and post-intervention in both groups. Data analysis was conducted using SPSS (Version 26) with appropriate statistical tests applied. Results: The study revealed that moderate-intensity exercise positively impacted plasma renin levels. For the EG, the pre-test mean (M) and standard deviation (SD) were 42.18±7.87, increasing to 54.00±11.22 post-intervention. In contrast, the CG showed pre-test values of 58.78±37.01, which rose to 87.92±51.44 post-intervention. Conclusion: The findings suggest that moderate-intensity exercise leads to a significant increase in plasma renin levels, highlighting the physiological impact of exercise on the RAS.